Growth arrest of Epstein–Barr virus immortalized B lymphocytes by adenovirus-delivered ribozymes - Huang, Shuang (The National Academy of Sciences of the USA, 1997)
Epstein–Barr virus (EBV) infection is associated with several human diseases that involve unrestricted proliferation of B lymphocytes. EBV nuclear antigen 1 (EBNA-1) is expressed in all EBV-infected cells and plays an essential role in persistence of the EBV genome. EBNA-1 has also been reported to have oncogenic potential. As an approach for treating EBV infections, we examined the capacity of EBNA-1 ribozymes delivered by recombinant adenoviruses to suppress EBNA-1 expression and to block virus-induced B cell proliferation. In contrast to primary B cells, EBV-transformed B lymphoblastoid cell lines expressed αv integrins, the adenovirus internalization receptors, and were also susceptible to adenovirus-mediated gene delivery. Adenovirus delivery of a specific ribozyme (RZ1) to lymphoblastoid cell lines, suppressed EBNA-1 mRNA and protein expression, significantly reduced the number of EBV genomes, and nearly abolished cell proliferation in low serum. Adenovirus delivery of RZ1 also prevented EBV infection of an established EBV-negative B cell line. These studies demonstrate the potential use of adenovirus-encoded ribozymes to treat EBV-induced lymphoproliferative disorders.